Determinan Pengembangan Agribisnis Lada Putih di Kecamatan Air Gegas, Kabupaten Bangka Selatan - Paramitha, Annisa Pradnya; Agustina, Fournita; Sitorus, Rostiar; Evahelda, Evahelda; Muntoro, Muntoro (Universitas Galuh, 2026)
Air Gegas District has been designated as a white pepper-based rural development area in South Bangka Regency, Bangka Belitung Islands Province. Several studies have been conducted in this location, but these studies still show limitations due to the lack of discussion related to the determinants of white pepper agribusiness development as a consideration in developing strategies. The purpose of this study is to identify the determinants of white pepper agribusiness development in Air Gegas District, South Bangka Regency. This study was conducted in Air Gegas Village, Nyelanding Village, Delas Village, and Air Bara Village from January to August 2025 using a survey method. The data used in this study included primary data and secondary data collected through observation, interview, questionnaire, and documentary study from eight respondents. These data were analyzed using quantitative analysis with AHP accompanied by qualitative analysis. The results of this study indicate that the determinants of white pepper agribusiness development in South Bangka Regency consist of economic aspect, policy aspect, environmental aspect, social aspect, and technical aspect.